(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The use of renewable energy sources has been recognised as a key strategy for combating anthropogenic climate change. These energy sources are regarded as sustainable because they are naturally replenished and do not produce greenhouse gases. A vital step in achieving a low-carbon economy and addressing the global challenge of climate change is the implementation of renewable energy alternatives. This “green revolution” has been led by solar and wind energy. Incorporating new forms of renewable energy resources, such as wave and tidal energy, into the current mix of resources will aid in the transition to a fully 100% renewable energy future due to the abundance of such resources [1]. The complementarity assessment of renewable energy resources is crucial to design the optimal mix of these resources to meet load requirements in a jurisdiction. Multiple studies in the literature discuss the complementarity of renewable energy modalities for different jurisdictions. A review of such studies is presented in [2]. The review shows that most of these studies focus on wind, solar and hydro-power generation, with most focusing on just two of these three modalities. However, recent efforts have been made to assess the temporal complementarity of more than two resources, including marine renewable energy resources (wave and tidal) for US and UK jurisdictions [3], [4], concluding that marine renewable resources may have significant value to a future power system in terms of reduced balancing requirements and valuable capacity contribution. Similarly, Ireland may enjoy similar benefits from combined resource exploitation due to its island topography and good marine resource. Fig. 1, by way of example, presents renewable resource generation profiles (hourly resolution) for four seasonal weeks in 2017 and illustrates the potential benefits of combining marine resources at Inishtrahull Sound, Ireland. For example, wind and tidal are low in the autumn week (highlighted section), while wave and solar resources are available. However, the summer week sees low wind and wave resources, while tidal and solar provide complementary benefits. Another critical aspect of the complementarity studies is the set of metrics and indices used to assess the complementarity. Such metrics and indices are reviewed in [5]. Correlation coefficients are commonly used in the literature to evaluate complementarity between energy sources. However, there are several issues related to the correlation metrics reported in the literature, including the inability to handle nonlinearities in the data and the inability to handle more than two resources [6], to name a few. In this paper, we present a complementarity assessment of the four renewable resources, i.e. wave, tidal, wind and solar, around the island of Ireland (including Northern Ireland) using the new complementarity indices based on the mathematical concept of the total variation [6], which allow for complementarity assessment of more than two resources. We also comment on the possible benefits of the temporal characteristics of the marine renewable resources on the Irish generation mix. • Please see attached file for Figures and references.